Pelaksanaan Proses Kedatangan Kapal MT. Esteem Energy di Pelabuhan Pulau Laut oleh PT. Maritime Network Indonesia Cabang Kota Baru: Penelitian - Dafid Ginting; L. Baktiar Gokmahot (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The implementation of the arrival of MT. Esteem Energy at Pulau Laut Port by PT. Maritime Network Indonesia Kotabaru Branch is a crucial operational activity that requires careful planning and coordination between stakeholders. This study aims to analyze the determining factors for the success of the ship's arrival, including ETA accuracy, communication and coordination effectiveness, dock facility readiness, compliance with maritime regulations, environmental conditions, and the professionalism of the ship's crew and agents. The research was conducted through field observations and literature studies of maritime literature and regulations. The results of the study indicate that the success of the operation is influenced by the synergy of technical, administrative, and human resource factors. Good planning, timely information exchange, regulatory compliance, and effective coordination between parties play an important role in improving the efficiency, safety, and punctuality of ship arrivals.